ازدواجيّة الأنا والآخر في التكوينات الرمزيّة لشعر الطبيعة عند الصوفيّة (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يتناول البحث مجموعة من نصوص الطبيعة عند صوفيّة القرنين السادس والسابع الهجريّين، فيقف على رموزها وإحالاتها، من طيور وحيوانات وأمكنة، بهدف الكشف عن أحوال الصوفيّ وهو إزاء مفردات الطبيعة هذه -بوصفها تجلّيات لواجد الوجود- بين ميل إليها وشوق إلى الاتحاد بأديمها، وبين إعراض عنها ونفور من مادّيّتها، وكأنّه يحاول الارتحال منها إليها بها، فإمّا أن ينظر إليها بعين المحايث لها، المنتمي إليها، بفعل جمالها الذي هو –حقيقة- عائد إلى جمال مبدعها، وإمّا أن ينظر إليها بعين المفارق لها، الزاهد بها، إذ هو السالك في طريق المعرفة الإلهيّة، يسعى إلى الاتصال بالذات الخالقة، والعودة إلى الرحم الأولى، من خلال الالتفاف على القيمة الزمنيّة، وتحقيق المستقبل بإعادة إنتاج الماضي في كلّ آن. This research handles a group of Sufi texts about nature in the sixth and seventh century of the hegira. It concentrates on the symbols and significance of nature factors, such as birds, animals and places. All of that is to show the Sufi's way of thinking when using such factors, because they all have one indication: "GOD". Therefore, we find the Sufi either eager to meet the nature and trying to unite with the soil, or having rejection and alienation of its sensuality as an attempt to leave it, but actually it is the only direction to go. On one occasion, he deals with it as a close person to whom he belongs because of its beauty which symbolizes the beauty of God. On another occasion, he abstains from and leaves nature because he is seeking to know God, to connect with God the creator and to go back to the first uterus through neglecting the time and reaching the future by reproducing the past.